Exploring varicella zoster virus proteome for construction and validation of a multi-epitope based subunit vaccine using multifaceted immunoinformatics approaches - Yassir A. Almofti; Amna A. Ibrahim; Nuha A. Mahmoud; Abdelmajeed M. Elshafei; Nosiba Ibrahim; Ibrahim Albokhadaim; Saad Shousha; Ahmed O. Alameen; Nawal Elkhair; Mahmoud G. El Sebaei; Mahmoud Kandeel; Samir Alhojaily; et al. (PLoS ONE, 2025)
Varicella zoster (VZ) is a viral disease caused by varicella zoster virus (VZV) that is related to alphaherpesvirus subfamily. VZV causes a neurotropic disease in humans. The aim of this work was to stimulate the human immune system by developing a multi-epitope vaccine based on five VZV surface proteins. Multiple immunoinformatics techniques were applied to assess B-cell and T-cell epitopes. The population coverage of each T-cell epitope was analyzed and the results showed high population coverage scores. The vaccine consists of 615 amino acids and it was antigenic and non-allergenic. The vaccine’s hydrophilicity, stability, presence of aliphatic side chains, and thermal stability were all determined through an analysis of its physical and chemical characteristics. Also the vaccine demonstrated the least homology to human proteome (11%). Using the PSIPRED server and the Ramachandran plot, the vaccine’s secondary and tertiary structures were predicted, enhanced, and validated. The structural errors were assessed using the ProSA web tool. Furthermore, the vaccine’s solubility was higher than that of the E. coli proteins. Following immune simulation, there were significant amounts of T-cells, INF-γ, IL-2, and antibodies. Significant docking scores were obtained for each predicted epitopes and for the vaccine when docked to TLR4 chains. The TLR4-vaccine complex was highly stable according to molecular dynamic modeling. In silico cloning was performed to assess the vaccine’s expression in the pET28a(+) vector, and the cloning results were efficient for translation. To ascertain the vaccine’s effectiveness, in vivo and in vitro investigations, including clinical trials are required.